2013
DOI: 10.1186/1471-2164-14-789
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel transcripts and noncoding RNAs in bovine skin by deep next generation sequencing

Abstract: BackgroundDeep RNA sequencing (RNAseq) has opened a new horizon for understanding global gene expression. The functional annotation of non-model mammalian genomes including bovines is still poor compared to that of human and mouse. This particularly applies to tissues without direct significance for milk and meat production, like skin, in spite of its multifunctional relevance for the individual. Thus, applying an RNAseq approach, we performed a whole transcriptome analysis of pigmented and nonpigmented bovine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(147 citation statements)
references
References 73 publications
(92 reference statements)
9
135
2
Order By: Relevance
“…The central role of miRNAs in skeletal muscle development has been demonstrated by the detrimental consequences of Dicer deletion in embryonic skeletal muscle [42][43][44]. RNA-Seq technology has allowed the discovery and analysis of noncoding RNAs, and differential methods have been developed to identify novel lncRNAs in RNA-Seq data [45,46]. Although many studies have highlighted the important roles of lncRNAs indifferent tissues [47,48], little is known about the biological function and significance of lncRNAsduring skeletal muscle development in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…The central role of miRNAs in skeletal muscle development has been demonstrated by the detrimental consequences of Dicer deletion in embryonic skeletal muscle [42][43][44]. RNA-Seq technology has allowed the discovery and analysis of noncoding RNAs, and differential methods have been developed to identify novel lncRNAs in RNA-Seq data [45,46]. Although many studies have highlighted the important roles of lncRNAs indifferent tissues [47,48], little is known about the biological function and significance of lncRNAsduring skeletal muscle development in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies have examined the occurrence and potential functions of lncRNAs in ruminant livestock species [130][131][132]. A pioneer study screened reconstructed transcript assemblies of bovine-specific expressed sequence tags and identified 449 putative lncRNAs located in 405 intergenic regions [130].…”
Section: Long Non-coding Rna In Mammary Gland Development and Lactatimentioning
confidence: 99%
“…A pioneer study screened reconstructed transcript assemblies of bovine-specific expressed sequence tags and identified 449 putative lncRNAs located in 405 intergenic regions [130]. Following this initial study, Weikard et al [131] used RNA sequencing technique and identified 4848 potential lncRNAs, which were predominantly intergenic (4365) in bovine skin. In another study, Billerey et al [132] characterized 584 lncRNAs in bovine muscle in addition to significant correlated expression between 2083 pairs of lncRNA/protein encoding genes.…”
Section: Long Non-coding Rna In Mammary Gland Development and Lactatimentioning
confidence: 99%
“…There are currently five broad categories of lncRNAs, namely ⅰ) sense or ⅱ) antisense, when overlapping one or more exons of another transcript on the same or opposite Long non-coding RNAs and hepatocellular carcinoma (Review) FU-JUN YU 1 , JIAN-JIAN ZHENG 2 , PEI-HONG DONG 3 and XIAO-MING FAN strand, respectively; ⅲ) bidirectional, when the expression of lncRNA and a neighboring coding transcript on the opposite strand is initiated in close genomic proximity; ⅳ) intronic, when the lncRNA is derived from an intron of a splicing transcript; and ⅴ) intergenic, when it lies in the genomic interval between two genes (21,22). To facilitate the search for lncRNAs, the currently available online databases including ncRNAs are listed in Table I.…”
Section: Characteristics Of Lncrnasmentioning
confidence: 99%